The Impact of Opportunity Zones on Commercial Investment and Economic Activity - Kevin Corinth; Naomi E. Feldman (Institute of Labor Economics (IZA), 2022)
A provision of the Tax Cuts and Jobs Act of 2017 offered tax incentives for investing in certain low-income areas in the United States called Opportunity Zones (OZs). The goal of this provision was to spur private investment in OZs in order to improve the economic well-being of their residents. This paper uses a regression discontinuity design to evaluate the impact of OZs on commercial investment and economic activity. Using data on the universe of all significant commercial investments in the United States, we find that OZ selection led to practically no increase in investment in OZs. These findings are supported by additional data from Mastercard that also show no evidence of increased business activity nor consumer spending. Overall, our findings suggest that the impact of OZs on economic improvement has thus far been limited.
Keywords: H53; E22; D61; 330; opportunity zones; investment; tax policy; poverty